Administration of Amyloid Precursor Protein Gene Deleted Mouse ESC-Derived Thymic Epithelial Progenitors Attenuates Alzheimer's Pathology - Zhao, Jin; Su, Min; Lin, Yujun; Liu, Haiyan; He, Zhixu; Lai, Laijun (Frontiers in Immunology, 2020)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder and the most common cause of dementia in the elderly. Although amyloid-beta (Aβ) plaque deposition and chronic neuroinflammation in the central nervous system (CNS) contribute to AD pathology, neither Aβ plaque removal nor anti-inflammatory therapy has shown much clinical success, suggesting that the combinational therapies for the disease-causative factors may be needed for amelioration. Recent data also suggest that systemic immunity in AD should be boosted, rather than suppressed, to drive an immune-dependent cascade needed for Aβ clearance and brain repair. Thymic epithelial cells (TECs) not only play a critical role in supporting T cell development but also mediate the deletion of autoreactive T cells by expressing autoantigens. We have reported that embryonic stem cells (ESCs) can be selectively induced to differentiate into thymic epithelial progenitors (TEPs) in vitro that further develop into TECs in vivo to support T cell development. We show here that transplantation of mouse ESC (mESC)-TEPs into AD mice reduced cerebral Aβ plaque load and improved cognitive performance, in correlation with an increased number of T cells, enhanced choroid plexus (CP) gateway activity, and increased number of macrophages in the brain. Furthermore, transplantation of the amyloid precursor protein (APP) gene deleted mESC-TEPs (APP-/-) results in more effective reduction of AD pathology as compared to wild-type (APP+/+) mESC-TEPs. This is associated with the generation of Aβ-specific T cells, which leads to an increase of anti-Aβ antibody (Ab)-producing B cells in the spleen and enhanced levels of anti-Aβ antibodies in the serum, as well as an increase of Aβ phagocytosing macrophages in the CNS. Our results suggest that transplantation of APP-/- human ESC- or induced pluripotent stem cell (iPSC)-derived TEPs may provide a new tool to mitigate AD in patients.